2017
DOI: 10.1089/acm.2016.0302
|View full text |Cite
|
Sign up to set email alerts
|

Serenoa repensfor Lower Urinary Tract Symptoms/Benign Prostatic Hyperplasia: Current Evidence and Its Clinical Implications in Naturopathic Medicine

Abstract: The totality of evidence includes favorable patients' response from clinical experience, impact of placebo effect, early positive studies, subjective nature of symptom reporting, pharmacological properties of S. repens, and potential synergistic effects when combined with other therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 36 publications
0
17
0
3
Order By: Relevance
“…Equisetum arvense extract 5α-reductase inhibitor [44] Fenugreek oil Trigonella foenumgraecum oil Anti-inflammatory, antioxidant, antifungal, and antibacterial properties [45] Tall oil fatty acids Tall oil fatty acid β-Sitosterol component may be an effective 5-alpha reductase inhibitor [46] Green tea extract with 95% EGCG Camellia sinensis leaf extract Phytoconstituent epigallocatechin 3-gallate is a 5-α reductase inhibitor [47] Saw palmetto Serenoa serrulata Inhibits both isoforms of 5-α reductase, preventing conversion of testosterone to its active form, DHT, and also promotes hair follicle vascularization [48,49] Eclipta alba oil Eclipta alba (bhringraj oil)…”
Section: Horsetail Extractmentioning
confidence: 99%
“…Equisetum arvense extract 5α-reductase inhibitor [44] Fenugreek oil Trigonella foenumgraecum oil Anti-inflammatory, antioxidant, antifungal, and antibacterial properties [45] Tall oil fatty acids Tall oil fatty acid β-Sitosterol component may be an effective 5-alpha reductase inhibitor [46] Green tea extract with 95% EGCG Camellia sinensis leaf extract Phytoconstituent epigallocatechin 3-gallate is a 5-α reductase inhibitor [47] Saw palmetto Serenoa serrulata Inhibits both isoforms of 5-α reductase, preventing conversion of testosterone to its active form, DHT, and also promotes hair follicle vascularization [48,49] Eclipta alba oil Eclipta alba (bhringraj oil)…”
Section: Horsetail Extractmentioning
confidence: 99%
“…On the contrary, some authors described that Serenoa repens extracts have not shown more effectiveness than placebo in the treatment of BPH [24][25][26]. However, more recent data favor the use of Serenoa repens extracts in milder BPH cases with promising results [27].…”
Section: Discussionmentioning
confidence: 99%
“…S. repens'in aktif bileşikleri ağırlıklı olarak serbest yağ asitleri (laurik asit, oleik asit, miristik asit, palmitik asit ve linoleik asit) ve fitosterollerdir (betasitosterol, kampesterol ve stigmasterol) [45]. [6].…”
Section: Bph'de Kullanılan Fitoterapötikler Veunclassified